Level of Plasma Tissue Factor Pathway Inhibitor is Inversely Correlated With Intraarterial Diastolic Pressure in Subjects Who Underwent Coronary Angiography - Ito, Masaaki; Nakano, Takeshi; Ozaki, Morihiro; Masuoka, Hiroshi; Kawasaki, Atsushi; Kamei, Shigeru (JAPANESE CIRCULATION JOURNAL, 2001)
There are only a few studies of the relationship between hemostatic abnormalities and intraarterial pressure, so the present study investigated the association of various newer lipid and hemostatic variables with intraarterial pressure levels. Levels of total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol, triglyceride, lipoprotein-(a), remnant-like particle cholesterol, cholesteryl ester transfer protein, uric acid, blood glucose, fibrinogen, free form of tissue factor pathway inhibitor (TFPI), C-reactive protein, serum amyloid A protein, anti-Chlamydia pneumoniae immunoglobulin G and immunoglobulin A, and apolipoproteins (apo) A-I, B, and E were measured in 176 patients who underwent diagnostic coronary angiography. Intraarterial blood pressure was determined from central aortic pressure using a standard fluid-filled catheter-external transducer system. Multivariate regression analyses showed that TFPI level was the only independent factor associated with aortic diastolic pressure. The linear regression equation demonstrated a significant negative correlation of TFPI level with aortic diastolic pressure (r=−0.395, p=0.0011). With respect to the association with other parameters, the TFPI level showed significant correlations between the HDL-C level and the apo A-I level, both in the overall patients and in the patients with coronary artery stenosis. This is the first evidence that the level of the plasma free form of TFPI is inversely correlated to aortic diastolic pressure. (Jpn Circ J 2001; 65: 165 - 170)